Strong association between genotype F and hepatitis B virus (HBV) e antigen-negative variants among HBV-infected argentinean blood donors - França, Paulo H. C. (2004)
Fil: França, Paulo H. C. Universidade Federal do Rio de Janeiro. Departamento de Virologia; Brasil.